Factors and mass ratio analyses for Reactive Blue 19 dye decolorization using ozone: an experimental and analytical modelling approach - Lopes, Mayara Sakamoto [UNESP]; Moruzzi, Rodrigo Braga [UNESP]; Conceicao, Fabiano Tomazini [UNESP]; Gabriel Silva, Mariana Scicia [UNESP]; Pereira Antunes, Maria Lucia [UNESP] (Assoc Brasileira Engenharia Sanitaria Ambiental, 2019)
Dyes highly reduce sunlight penetration into the stream, and consequently affect photosynthesis and oxygen transfer into water bodies. An experimental and analytical modelling approach to Reactive Blue 19 (RB19) removal using ozone was carried out. For this purpose, factors and mass ratio analyses were assessed based on batch assays experiments. Removal efficiency increased from 64 to 94% when the dosage increased from 38.4 to 153.6 mg O-3.L-1. Results showed that RB19 is more efficiently removed when initial pH is 7. The rate of RB19 removal decreased as the initial dye concentration increased. Kinetic studies showed that the ozonation of RB19 was a pseudo first-order reaction with respect to the dye, and the apparent rate constant declined logarithmically with the initial dye concentration. Mass ratio studies showed that, for the empirical analysis, the power law equation was adequate to describe mass ratio over time and the analytical analysis suggests that the process is influenced by mass transfer in the liquid film as well as in the bulk fluid.
Keywords: reactive dye; ozone; decolorization factors; kinetics and mass ratio